Effectiveness of Tranexamic Acid in intraoperative bleeding reduction in c-section patients (Boletin Médico de Postgrado, 2020)
In order to determine the effectiveness of tranexamic acid (TA) in the reduction of intraoperative bleeding in patients undergoing cesarean section (C-section) admitted to the Obstetric Emergency Service of the Hospital Central Universitario Dr. Antonio Maria Pineda we performed a controlled, single blind, clinical trial with 30 patients who were randomly assigned in two groups: group A received TA and group B received crystalloids, 30 minutes before surgery. Lower mean hemoglobin post-surgery values compared to baseline were observed in the group that did not receive TA. Adverse effects of TA were nausea (53.3%), tachycardia (33.3%) and facial edema (6.6%). No patient required the administration of blood products during the transoperative period. Average observed blood losses in the AT and control groups were 390 ± 160.5 cc to 773.3 ±174.9 cc, respectively (p = 0.000). We conclude that tranexamic acid decreases observed blood losses in patients undergoing C-section.
Keywords: tranexamic acid; intraoperative bleeding; cesarean section